2010
DOI: 10.2353/jmoldx.2010.090184
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Villous Morphology Associated with Triple Trisomy of Paternal Origin

Abstract: The vast majority of trisomies in spontaneous abortions (SAB) are single and of maternal origin , most frequently due to meiosis I errors. Triple trisomies are exceedingly rare (ϳ0.05% of spontaneous abortions) , most often of maternal origin , and associated with increased maternal age. Some trisomic SAB specimens can exhibit abnormal villous morphology simulating a partial hydatidiform mole , a distinct form of hydatidiform mole characterized by diandric triploidy. A SAB specimen from a 27-year-old woman, G1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Also for academic interest, further investigation of the non-molar specimen with double trisomy involving chromosomes 7 and 13 (which was initially interpreted as a partial hydatidiform mole by morphology) via singlenucleotide polymorphism array analysis identified triple trisomy of paternal origin involving chromosomes 7, 13, and 20. 42 There were 21 cases with more complex genotypes than those of typical molar and non-molar specimens. Of these, 14 were classifiable as forms of androgenetic/biparental mosaic specimens (11 of these are described in detail in our previous study).…”
Section: Modern Pathology (2014) 27 238-254mentioning
confidence: 99%
See 1 more Smart Citation
“…Also for academic interest, further investigation of the non-molar specimen with double trisomy involving chromosomes 7 and 13 (which was initially interpreted as a partial hydatidiform mole by morphology) via singlenucleotide polymorphism array analysis identified triple trisomy of paternal origin involving chromosomes 7, 13, and 20. 42 There were 21 cases with more complex genotypes than those of typical molar and non-molar specimens. Of these, 14 were classifiable as forms of androgenetic/biparental mosaic specimens (11 of these are described in detail in our previous study).…”
Section: Modern Pathology (2014) 27 238-254mentioning
confidence: 99%
“…40 In addition, some non-molar specimens with cytogenetic abnormalities such as trisomy can simulate partial hydatidiform moles, causing problems in diagnostic reproducibility. 41,42 In 2007, we began a prospective analysis of all potentially molar products of conception specimens encountered on the Gynecologic Pathology Service of The Johns Hopkins Hospital, Baltimore, MD using immunohistochemical analysis of p57 expression and molecular genotyping with short tandem repeat markers. 25,31,43 The current study summarizes the results of nearly 6 years of analysis, providing a summary of the characteristics of a large series of hydatidiform moles and non-molar specimens assessed by these techniques as well as the assessment of the performance of these methods in clinical practice.…”
mentioning
confidence: 99%
“…Prior to the discovery of the molecular basis of PHM, association of trisomies (trisomy 2 in particular) with hydatidiform moles has also been suggested (8). A recent case report described a triple trisomy of paternal origin mimicking PHM (7). However, other studies have not found significant differences in the villous morphology based on the parental origin of the extra chromosomes in trisomic gestations (9).…”
mentioning
confidence: 96%
“…The morphologic overlaps between PHM and chromosomal trisomies have long been recognized (5)(6)(7)(8)(9)(10). In addition, other morphologic mimics of PHM include complete hydatidiform mole (CHM), diploid hydropic abortions and digynic triploidy in early gestations, and placental mesenchymal dysplasia at later gestational age (GA) (11).…”
mentioning
confidence: 98%
“…Despite these differences, a substantial degree of morphologic overlap exists between these 2 types of HMs. In addition, distinction of HMs from NMs can be problematic in several situations, including: (a) products of conception specimens (POCs) with abnormal villous morphology (a nonmolar type of villous abnormality having some morphologic features suggestive of a PHM but lacking the diandric triploidy required for a definitive diagnosis of PHM, sometimes attributable to other genetic abnormalities such as trisomy) 7,46,49,51 ; (b) early nonmolar abortuses with prominent trophoblastic hyperplasia; (c) hydropic abortuses; and (d) mosaic/chimeric conceptions. 25,26,30,51,57 These problems are partially because of the fact that histologic criteria for diagnosis of HMs are imperfect, not all pathologists apply criteria similarly, and because the histologic appearance can vary depending on gestational age.…”
mentioning
confidence: 99%